Pemanfaatan Augmented Reality (AR) Sebagai Media Pembelajaran Benda Padat, Cair dan Gas - Togihon J.P. Simaremare; Yuliana Emi; Yohanes Bahari; Warneri Warneri (Departement of Mathematics Education, 2024)
The rapid development of technology encourages the diffusion of innovation in the world of education, including in learning methods. One phenomenon of innovation that is used and continues to increase is the use of Augmented Reality (AR) media as an interactive learning media. The purpose of this study is to measure the effectiveness of AR learning media and student responses after using the learning media. This research uses quantitative descriptive method. AR learning media will be tested on 18 third grade students of SD Tunas Bangsa Kubu Raya, which is divided into four groups. The instruments used are questionnaires to measure students' responses and post-test to evaluate students' knowledge improvement after using AR learning media. In conclusion, by using AR media in learning material about solid, liquid and gas objects, students showed a significant increase in understanding when doing the post-test. Students are able to understand that solid objects do not necessarily have to be hard, but have other characteristics that distinguish them from liquid and gas substances. The results of the student response questionnaire to AR learning media are 82.2% with a very good response category.